Calculation Schemes for Determining Contact Stresses in Railway Rails - Valerii Kosarchuk; Volodymyr Tverdomed; Olha Bambura (Applied Sciences)
One of the tasks of ensuring the safe and sustainable operation of railway transport is to assess the life cycle of the railway track and its elements—in particular, rails. It is known that the main cause of their failure is the development of defects that arise as a result of contact of rails with the wheels of rolling stock—contact fatigue defects. Modern approaches to predicting the contact-fatigue endurance of railway rails and wheels of rolling stock are based on the use of the kinetic theory of damage. The basis of such predictions is the calculation of the stress–strain state of rails under the action of combinations of external force and temperature influences, which is associated with the need to solve spatial boundary value problems of contact interaction. The complexity of such problems necessitates the use of numerical methods, such as the finite element method in particular, for their solution. This paper considers the features of constructing calculation schemes for such problems. Attention is primarily paid to assessing the influence of some design parameters of the rail track and wheels on the magnitude and distribution of stresses in the contact zone. The results will be useful for understanding the physical processes of damage accumulation, the occurrence and development of defects in rails and wheels, as well as for developing methods for predicting the contact fatigue endurance of important elements of railway infrastructure.